Networking for Power Grid and Smart Grid Communications: Structures, Security Issues, and Features - Basnet, Biswash; Sen, Varsha (Recent Research Reviews Journal, 2025)
The evolution from traditional to smart grid systems has radically changed communication architectures. It enables secure, efficient, and resilient energy infrastructures. Unlike the centralized, unidirectional communication practices typical of traditional grids with minimal automation, modern smart grids use tiered, bidirectional networks allowing real-time control, integration of distributed energy resources (DER), and active consumer participation. The drive for this development arises from the growing use of renewable energy resources, electric vehicles, and sophisticated digital metering technologies. End-to-end communication architectures now underpin grid reliability, interoperability, and cybersecurity. This research explores the end-to-end architecture of traditional and smart grids, including access technologies, protocol layers (e.g., IEC 61850, Modbus, DNP3), and hierarchical network domains such as the Home Area Network (HAN), Neighbourhood Area Network (NAN), and Wide Area Network (WAN). Physical transmission mediums, key cybersecurity challenges, and standards like IEC 60870 are also discussed. Case studies of real implementations, emerging protocols, and security issues are analyzed to clarify directions toward intelligent, scalable, and self-healing grid communication infrastructures.
Keywords: Protocols; Cybersecurity; Grid Resilience; Interoperability; Automation; AMI; PMU; SCADA; DNP3